2017
DOI: 10.1590/1809-4392201601993
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of climate change impacts on water resources of the Purus Basin in the southwestern Amazon

Abstract: Knowledge about water resources is critical for climate adaptation in face of long-term changes and more frequent extreme events occurrence. During the major droughts of 2005 and 2010, a large epicenter was located in the southwestern Amazon over the Purus River Basin. In this sense, we conducted a hydrological simulation in this basin to assess the climate change impacts on its water resources throughout the 21st century. The water balance was simulated using the Distributed Hydrological Model (MHD-INPE). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
(47 reference statements)
1
11
0
3
Order By: Relevance
“…Similar to this work, climate change is projected to reduce the Tapajós river discharge for most of the scenarios, except for one model that showed a significant increase in the discharge (Mohor et al, 2015), and reductions in discharge were also found for Purus basin (Dalagnol et al, 2017).…”
Section: Rq 4 What Are the Potential Effects Of Secondary Regrowth Afsupporting
confidence: 64%
See 2 more Smart Citations
“…Similar to this work, climate change is projected to reduce the Tapajós river discharge for most of the scenarios, except for one model that showed a significant increase in the discharge (Mohor et al, 2015), and reductions in discharge were also found for Purus basin (Dalagnol et al, 2017).…”
Section: Rq 4 What Are the Potential Effects Of Secondary Regrowth Afsupporting
confidence: 64%
“…Also, except for leaf scale measurements that included some pioneer species (Kunert et al, 2015), literature still lacks reports of direct observations of fluxes in secondary vegetation areas in Amazonia. Additionally, studies that investigated the impacts of climate variability and land use conversion on river discharge (Dalagnol et al, 2017;Mohor et al, 2015;Siqueira Jr et al, 2015) did not consider the impact of secondary vegetation regrowth on the water cycle, which may become an important land use in the amazon in the near future (Aguiar et al, 2016).…”
Section: Knowledge Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…The average temperature is 27 ºC. Minimum rainfall and temperature are in July (Dalagnol et al, 2017). 15 …”
Section: −1mentioning
confidence: 99%
“…Esses impactos foram detalhados no relatório do IPCC (2014) para a América do Sul, com destaque para a redução da umidade média dos solos, alterações nos padrões de precipitação principalmente nos fatores de variabilidade e intensidade, o que afetaria diretamente a disponibilidade e distribuição temporal das vazões superficiais (ANA, 2016). Alguns estudos em escala de bacias hidrográficas alinham-se com essas projeções globais, destaca-se Nóbrega et al (2011) na bacia do Rio Grande, sudeste do Brasil e Dalagnol et al (2017) na bacia do Rio Purus, sudoeste da Amazônia.…”
Section: Introductionunclassified